Educational Policy: Egalitarian or Elitist? - Minseong Kim; Herschel Grossman (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
This paper offers an explanation for observed differences across countries in educational policies and in resulting interpersonal distributions of human capital. We analyse a generalequilibrium model in which, as a result of the apportionment of natural ability, nurturing, and publicly financed education, some people can be well endowed with human capital, whereas other people are poorly endowed with human capital. We assume that people can choose to be either producers or predators. Because an increase in a person's human capital makes predation a less attractive choice for that person, it is possible that by using some of their human capital to educate the poorly endowed people the well endowed people can increase their own consumption. More interestingly, our theory predicts that, if producers are able to enforce a collective choice that takes advantage of the deterrent effect of allocating resources to guarding against predators, then the well endowed people prefer a relatively egalitarian educational policy that increases the human capital of all of the poorly endowed people. Such an educational policy either decreases the cost of deterring predation or makes deterrence possible. In contrast, if producers or small subsets of producers individually choose the amount of their resources to allocate to guarding, taking the ratio of predators to producers as given, then the well endowed people prefer an elitist educational policy that, if it has a redistributional component, decreases the number of poorly endowed people, thereby decreasing the number of predators, without increasing the human capital of the remaining poorly endowed people. These implications seem to be consistent with the facts about differences across countries in educational policy.
Keywords: 330